Potency of cinnamaldehyde of cinnamon oil as an antidiabetic compound - Ngadiwiyana .; Ismiyarto .; Nor Basid A. Prasetya; Purbowatiningrum R. S. (Indonesian Journal of Pharmacy, 2011)
Cafeic  and  cinnamic  compounds  have  been  reported  to give  an  excellent performance  as  α-glucosidase  inhibitor. Inhibition  of  α-glucosidase  in  the intestine of mammals are able to lower blood sugar  levels of the carbohydrates metabolism  so  it  can  reduce  postprandial  hyperglycemia  which  can  prevent chronic  complications  of  Diabetes  Mellitus  (DM). Based  on  cafeic  and  cinnamic structures in terms of organic chemistry and economic considerations, it can be offered  a  very  promising  alternative  to  provide  their  derivative  compounds  of cafeic  from  cinnamon  oil,  which  is  cinnamaldehyde.  Cinnamaldehyde  can  be isolated  from  cinnamon  oil  by  addition  of  sodium  bisulphite  to  provide  salt compounds  which  are  separated  easily  from  the  mixed system. The  aldehyde compound  can  be  obtained  by  acid  addition. Structure  elucidation  of cinnamaldehyde was done by mean of an infra red spectrophotometer and a gas chromatography-mass  spectroscopy. Activity  test  of  anti-diabetic  compounds was  carried  through  the  measurement  of  the  concentration  of  minimum resistance against α-glucosidase activity. Cinnamaldehyde which is isolated from cinnamon  oil  was  yellowish  oil  and  cinnamaldehyde’s yield  was  up  to  42.67%, and its purity was 99.8723%. Structure elucidation of cinnamaldehyde by mean of infra red spectrophotometer (FTIR) showed carbonyl vibration at 1676 cm-1, -C-H  aldehyde  at  2813.9  cm-1 and  2742.6  cm-1.  From  mass  spectra,  it  can  be known  that  cinnamaldehyde  had  M+ 132  with  m/z  of  main  fragmentation  were 131,  103,  77,  and  51.  Inhibition  activity  of  α-glucosidase  test  showed  that inhibitory concentration at 50 ppm of cinnamaldehyde was 93.29%, and IC50 to the α-glucosidase was 27.97 ppm.Key words :cinnamon oil, cinnamaldehyde, anti-diabetic